2015
DOI: 10.5812/ircmj.26622
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of Bacterial Antibiotic Sensitivity After Short-Term Exposure to Diagnostic Ultrasound

Abstract: BackgroundMany pathogenic bacteria show different levels of antibiotic resistance. Furthermore, a lot of hospital-acquired infections are caused by highly resistant or multidrug-resistant Gram-negative bacteria. According to WHO, patients with drug-resistant infections have higher morbidity and mortality. Moreover, patients infected with bacteria that are resistant to antibiotics considerably consume more healthcare resources.ObjectivesIn this study, we explored a physical method of converting drug-resistant b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 17 publications
0
5
1
Order By: Relevance
“…nitrofurantoin, nalidixic acid, and gentamicin antibiotics were used. The results showed that S. aureus was resistant to erythomycin and sensitive to vancomycin [27]. In this study, ultrasound waves altered the antimicrobial susceptibility in staphylococcus bacteria that is inconsistent with the present study findings.…”
Section: Discussioncontrasting
confidence: 99%
“…nitrofurantoin, nalidixic acid, and gentamicin antibiotics were used. The results showed that S. aureus was resistant to erythomycin and sensitive to vancomycin [27]. In this study, ultrasound waves altered the antimicrobial susceptibility in staphylococcus bacteria that is inconsistent with the present study findings.…”
Section: Discussioncontrasting
confidence: 99%
“…On the other hand, we have previously addressed the bioeffects of the exposure of bacteria to electromagnetic radiations and investigated different aspects of the challenging issue of the ionizing or nonionizing radiation-induced alterations in the susceptibility of microorganisms to antibiotics. 19,[32][33][34] In the current study, the pattern of the response of E coli to Wi-Fi and RF simulator radiation was identical. The maximum differences in the diameters of inhibition zones were observed between 6 and 9 hours of the bacterial exposure to radiation (Figures 1 and 2).…”
Section: Resultsmentioning
confidence: 95%
“…On the other hand, we have previously addressed the bioeffects of the exposure of bacteria to electromagnetic radiations and investigated different aspects of the challenging issue of the ionizing or nonionizing radiation-induced alterations in the susceptibility of microorganisms to antibiotics. 19 , 32 – 34…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, we have previously reported that the observed decrease in diameter of the zone of inhibition in K. pneumoniae after exposure to mechanical ultrasound waves, can be explained as the induction of adaptive response. 13…”
Section: Discussionmentioning
confidence: 99%